The Weekend Effect in Carotid Endarterectomy for Symptomatic Carotid Stenosis. (April 2022) - Kim, Young; Lee, Sujin; Tanious, Adam; Decarlo, Charles S.; Png, Chien-Yi Maximilian; Patel, Shiv S.; Mohapatra, Abhisekh; Dua, Anahita
Background: Recent studies report a limited window in which carotid endarterectomy (CEA) provides the greatest benefit for symptomatic carotid stenosis. Given the time-sensitive nature of CEA for symptomatic stenosis, it is important to understand whether patient outcomes are adversely affected by undergoing CEA over the weekend. Currently, it is unclear whether CEA is impacted by the "weekend effect" phenomenon.Methods A multi-institutional database was queried for all patients undergoing CEA for symptomatic carotid artery stenosis from 2015 to 2020 via ICD-9 codes. A total of 288 patients were identified during the study period. Univariate and multivariate analysis were used to compare outcomes based on weekend vs weekday surgery.Results A total of 261 patients (90.6%) underwent weekday CEA, as compared to 27 (9.4%) on the weekend. There were no differences in age, race, gender, or medical comorbidities between groups. Primary surgeon specialty was predominantly vascular surgery (77.0% weekday and 74.1% weekend) followed by neurosurgery (19.9% weekday and 25.9% weekend). Operative time was similar between groups (3.1 (weekday) vs 2.9 hr (weekend), P = .33) as well as estimated blood loss (100 vs 100 mL, P = .54). Hospital length of stay did not differ between groups ( P = .69). Combined stroke and 30-day mortality rate was 2.0% on weekdays, compared to 3.7% on weekends ( P = .75). On multivariate analysis, weekend surgery was not predictive of postoperative stroke or 30-day mortality (odds ratio .11 [95% CI: −1.57 to 1.85], P = .90).Conclusion In our multi-institutional experience, we did not identify a "weekend effect" in patients undergoing CEA for symptomatic carotid artery stenosis. Surgical revascularization should not be withheld on account of a weekend procedure in similar academic medical centers.